Superação de dormência e seleção de híbridos experimentais de morangueiro - Zeist, Ricardo Antônio (2019)
With the increasing development of the strawberry crop in Brazil in the last years and the dependence on cultivars imported for cultivation, the cost of crop production is increasingly increasing, thus reducing farmers' profits. The search for national cultivars adapted to the climatic conditions has been an alternative for strawberry production in Brazil. One of the main obstacles in breeding programs is the difficulty of germination of achenes, which present tegument dormancy and natural germination of 10 to 20%. Thus the objectives of this work were 1 °: to test plant regulators in the dormancy dormancy and the development of strawberry seedlings; 2 °: to obtain and select F1 plants, which present productive potential equal to or higher than the currently planted imported cultivars. The chemical puncture with H2SO4 (98%) for 15 min and the use of acid Indol-3-Butyric Acid (Auxina) provided a positive effect on germination, and the Stimulate® bioregulator provided a positive effect on the development of strawberry seedlings. development of moran-gueiro seedlings. The cross between Camino Real and the pre-selected RVFS07, RVFS06, RVDA11, RVDA11, RVCA16 and RVCS44 clones resulted in 916 high potential hybrids, among which the RVCA16R-39, RVFS07R-61, RVCS44R-143 and RVCS44R- 110 have high productive potential and can be used in new adaptability and stability tests to be launched in the future.